Waterbody hydrodynamic and water quality modeling an introductory workbook and CD-ROM on three-dimensional waterbody modeling - Edinger, John Eric (Reston, Virginia ASCE Press, 2002)
This workbook provides software for a three-dimensional hydrodynamic and transport model that can be used to study the circulation in water bodies as influenced by inflows, outflows, tides, winds, salinity, and temperature. Coupled with the model is a dissolved oxygen depression model, a particulate-based nutrient and eutrophication model, and a sediment scour and deposition model The model is set up using provided input data files. The workbook goes through the steps of setting up an example application for its bathymetry, its input data file, and specification of the desired output, followed by execution of the example. Further example applications are presented showing the setup of the model for different types of water bodies and for the different water quality models provided in the software. The results of the 30 example applications are provided in example output folders. Following the example applications are chapters on the theoretical basis and formulation of the hydrodynamic and transport model, the first-order decay relationships, the surface heat exchange relationships, the dissolved oxygen depression model, the nutrient and eutrophication model, and the sediment scour and deposition model.
This title was originally sold with software enclosed on a CD-ROM. The software is included with the e-book as Supplemental Material.
Includes bibliographical references and index.
Keywords: Hydrodynamics -- Computer programs; Water quality -- Computer programs; Electronic books